Evaluation of budget support in Zambia: implementation, direct effects and political economy - Stefan Leiderer; Jörg Faust (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
This study - commissioned by the German Ministry for Economic Cooperation and Development (BMZ) – evaluates the direct effects (i.e. the direct and induced outputs) of budget support in Zambia. It forms part of a joint international evaluation of budget support in Zambia. The report focuses on strategies of the cooperating partners in providing budget support, the processes and structure of donor harmonization and alignment with government policies and systems, and the effects of budget support on induced outputs such as institutional performance, public financial management, and allocative and operational efficiency. The overall assessment of budget support in Zambia is positive: The evaluation concludes that budget support has helped to realize a number of objectives in Zambia, especially as a financing instrument supporting the national development strategy. At the same time, the evaluation also concludes that budget support could have been even more effective in Zambia, in particular as an instrument to promote good governance and effective state institutions. Weaknesses on the part of Zambian government as well as a lack of harmonization and coordination on the donor side have weakened the potential of the instrument in this respect.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Wirksamkeit und Evaluierung; Entwicklungshilfe; Öffentlicher Haushalt; Einführung; Entwicklungshilfekonditionen; Wirkungsanalyse; Neue politische Ökonomie; Sambia